Desertion in Time of Peace Against Soldier Indonesian National Army - Muhammad Ash Shiddik Azhari; Hambali Thalib; Muhammad Rustan (COMPENDIUM OF JUDGE MADE LAW, 2025)
This writing aims to: (1) To find out and analyze the qualifications of the crime of desertion in military criminal law. (2) To find out and analyze the judge's considerations in Decision No: 135-K / PM.III-16 / AD / X / 2022. The type of research used is normative legal research, a process to find a rule, legal principles, or legal doctrines. The results of the writing show that the Qualification of the Crime of Desertion in the Criminal Code is Article 87 paragraph (1) 2 of the Criminal Code, where the qualifications are First, Military; Second, Intentionally; Third, Carrying out absence without permission; fourth, In times of peace; and Fifth, Longer than thirty days. The judge's considerations in imposing a criminal sentence on the defendant include mitigating and aggravating considerations. There are three mitigating considerations from the judge: The defendant is frank and admits his mistakes. This is based on the judge's considerations which are of a legal nature, namely the defendant's statement. The defendant is still young and has never been convicted. This is based on the judge's considerations which are non-juridical, namely the Defendant's condition. The Defendant returned to the Unit by surrendering himself to Denpom Parepare. The Defendant's actions can affect the disciplinary development of other soldiers in the unit. Based on the judge's considerations which are juridical, namely witness statements. Writing recommendations: (1) For members of the Military to increase awareness and understanding of the importance of military discipline and responsibility and improve communication between superiors and subordinates. (2) For policy makers and decision makers to hold education and training programs to provide awareness and responsibility to members of the Military and to conduct periodic evaluations and monitoring of members of the Military.